Dicationic E4 Chains (E=P, As, Sb, Bi) Embedded in the Coordination Sphere of Transition Metals. Issue 12 (21st February 2018) - Dütsch, Luis; Fleischmann, Martin; Welsch, Stefan; Balázs, Gábor; Kremer, Werner; Scheer, Manfred
Abstract: The oxidation chemistry of the complexes [{CpMo(CO)2 }2 (μ, η 2 :η 2 ‐E2 )] (E=P (A ), As (B ), Sb (C ), Bi (D )) is compared. The oxidation ofA –D with [Thia] + (=[C12 H8 S2 ] + ) results in the selective formation of the dicationic E4 complexes [{CpMo(CO)2 }4 (μ4, η 2 :η 2 :η 2 :η 2 ‐E4 )] 2+ (E=P (1 ), As (2 ), Sb (3 ), Bi (4 )), stabilized by four [CpMo(CO)2 ] fragments. The formation of the corresponding monocations [A ] +, [C ] +, and [D ] + could not be detected by cyclic voltammetry, EPR, or NMR spectroscopy. This finding suggests that dimerization is fast and that there is no dissociation in solution, which was also predicted by DFT calculations. However, EPR measurements of2 confirmed the presence of small amounts of the radical cation [B ] + in solution. Single‐crystal X‐ray diffraction revealed that the products1 and2 feature a zigzag E4 chain in the solid state while3 and4 bear a central E4 cage with a distorted "butterfly‐like" geometry. Additionally, 1 can be easily and reversibly converted into a symmetric and an unsymmetric form. Abstract : Unprecedented dicationic E4 chains and cages (E=pnictogen) are obtained by the oxidation of [{CpMo(CO)2 }2 (μ, η 2 :η 2 ‐E2 )] complexes through E−E bond formation. The dicationic cores are free of organic substituents and are stabilized in the coordination sphere of molybdenum atoms.